Classroom Management #Karen: What Can Educators Learn From a Meme?. (2nd October 2022) - L. Deckman, Sherry; Aguilar, Lizette
Abstract : Much has been written about how race and the demographic mismatch of mostly white teachers teaching mostly Black and brown students has contributed to the over-disciplining of this same population of students. Further, research has shown that when students have teachers of the same race they are less likely to experience exclusionary discipline practices. While recent studies have considered the role of gender, along with race, in school discipline, the focus remains primarily on the gender and race of the students, with fewer studies considering specifically what it might mean for school discipline that U.S. teachers are mostly white women. This paper takes up that focus and applies the recent #Karen meme to an analysis of the school discipline gap, ultimately offering implications for education practitioners and researchers.